Money Demand in the United States. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1988)
This paper considers the demand for various monetary aggregates with a view to assessing their potential roles as intermediate variables for monetary policy. Illustrative estimates using a generalized autoregressive distributed lag model are presented. For M1, the results support an 'error correction' model. However, the demand function for M1 may still be subject to shifts due to the continuing process of financial reform and innovation. The demand function for M1A resulting from the particular empirical strategy used in this paper is not well behaved. The estimated equation for M2 is well behaved and robust, though the use of M2 as an intermediate target variable is questionable due to an inability accurately to control it.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet